2011
DOI: 10.1001/archsurg.2011.213
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating Preventable Death on the Battlefield

Abstract: To evaluate battlefield survival in a novel command-directed casualty response system that comprehensively integrates Tactical Combat Casualty Care guidelines and a prehospital trauma registry. Design: Analysis of battle injury data collected during combat deployments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
177
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 373 publications
(191 citation statements)
references
References 37 publications
4
177
0
10
Order By: Relevance
“…The resultant TCCC paradigm continues to save lives down-range. 2,8 A study of the TCCC-trained, 75 th Ranger Regiment found that 1.7% of regimental fatalities died of wounds, compared with 5.8% in the larger US military population (P = .02). 2 No Ranger fatality died from wounds potentially survivable through additional prehospital interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The resultant TCCC paradigm continues to save lives down-range. 2,8 A study of the TCCC-trained, 75 th Ranger Regiment found that 1.7% of regimental fatalities died of wounds, compared with 5.8% in the larger US military population (P = .02). 2 No Ranger fatality died from wounds potentially survivable through additional prehospital interventions.…”
Section: Discussionmentioning
confidence: 99%
“…2,8 A study of the TCCC-trained, 75 th Ranger Regiment found that 1.7% of regimental fatalities died of wounds, compared with 5.8% in the larger US military population (P = .02). 2 No Ranger fatality died from wounds potentially survivable through additional prehospital interventions. The TCCC training proved so effective that although exsanguinating hemorrhage remains the leading cause of possibly preventable combat death, fatalities from extremity hemorrhage decreased from 60% to 13.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Unfortunately many combat-type injuries, such as those seen during the Boston Marathon bombing, occur in the United States. 5 To address this, The Joint Committee to Create a National Policy to Enhance Survivability from Mass Casualty Shooting Events produced recommendations known as the Hartford Consensus I and II.…”
mentioning
confidence: 99%
“…Det kan vara att agera i extrem kyla eller värme och under mörker, att vara ensam vid omhändertagandet, att flera skadas samtidigt, och att tvingas begränsningar avseende sjukvårdsutrustning och/eller fördröjd avtransport från skadeplats (Kotwal et al, 2011). Dessutom påverkar alltid även den taktiska situationen omhändertagandet (Butler, 2003;Veliz, Montgomery & Kotwal, 2010).…”
Section: Militär Personalunclassified